2019
DOI: 10.1093/mnras/stz3280
|View full text |Cite
|
Sign up to set email alerts
|

Cusp or core? Revisiting the globular cluster timing problem in Fornax

Abstract: We use N-body simulations to revisit the globular cluster (GC) "timing problem" in the Fornax dwarf spheroidal (dSph). In agreement with earlier work, we find that, due to dynamical friction, GCs sink to the center of dark matter halos with a cuspy inner density profile but "stall" at roughly 1/3 of the core radius (r core ) in halos with constant-density cores. The timescales to sink or stall depend strongly on the mass of the GC and on the initial orbital radius, but are essentially the same for either cuspy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(78 citation statements)
references
References 46 publications
(58 reference statements)
8
68
2
Order By: Relevance
“…On average, our DM halo mass estimates are an order of magnitude larger than previous determinations based on the stellar kinematics of the Fornax dSph, which suggest a DM halo mass of few × 10 9 M (Goerdt et al 2006;Boldrini et al 2019;Meadows et al 2020). However, our estimates are in good agreement with the abundancematching result of Read et al (2019), who found a total mass of ∼2 × 10 10 M .…”
Section: The Dm Halo Of the Fornax Dsphcontrasting
confidence: 73%
See 2 more Smart Citations
“…On average, our DM halo mass estimates are an order of magnitude larger than previous determinations based on the stellar kinematics of the Fornax dSph, which suggest a DM halo mass of few × 10 9 M (Goerdt et al 2006;Boldrini et al 2019;Meadows et al 2020). However, our estimates are in good agreement with the abundancematching result of Read et al (2019), who found a total mass of ∼2 × 10 10 M .…”
Section: The Dm Halo Of the Fornax Dsphcontrasting
confidence: 73%
“…decay time-scales by assuming larger initial radii for the GCs rather than assuming that they formed at their present-day positions (e.g. Angus & Diaferio 2009;Cole et al 2012;Boldrini, Mohayaee & Silk 2019;Meadows et al 2020). However, the initial positions where the GCs were born are difficult to constrain due to the long time-scales involved.…”
Section: ; DImentioning
confidence: 99%
See 1 more Smart Citation
“…For the GC to merely arrive and survive in the centre after arrival, there are no strong requirements for the halo profile or orbital eccentricity. The time-scale for infall is to first order, set by the starting position in the host, with minimal dependence on the inner density profile slope (see also Meadows et al 2020). As shown in Section 5.3 however, there is a clear preference for the optimal solutions which also reproduce the GC structure (green points) to have initial starting positions for the GC of D gal, i 700 pc.…”
Section: Characteristics Of Successful Orbitsmentioning
confidence: 99%
“…This process of orbital inspiral is sensitive to the shape of the total density profile of the host galaxy, with the relatively high-mass ratios between GCs and dwarf galaxy hosts meaning that this process is expected to be important in the survival of the GC (Orkney et al 2019). For example, Petts, Read & Gualandris (2016) showed under which conditions the host galaxy's density profile may lead to the dynamical friction processes stalling, while Meadows et al (2020) further illustrated the similarity in dynamical friction time-scales in cored and cusped density profiles.…”
mentioning
confidence: 99%